COMPARISON OF GROWTH AND CONVERSION EFFICIENCY O:F THE FRESIDVATER PRAWN MACRO BRACHIUM MALCOLMSONII (H. MILNE EDWARDS) JUVENILES FED WITH FORMULATED AND COMMERCIAL FEEDS - SAMUEL, M. JOHN; SOUNDARAPANDIAN, P.; KONNUPANDI, T. (Journal of Indian Fisheries Association, 2015)
A nutritional study was carried out to know the feasibility of formulated and commercial feeds on the growth of juveniles of the freshwater prawn Macrobrachium malcolmsonii. Best relative growth rate was observed for feed 1 followed by feeds 2 and 3. Animals fed with feed I showed higher production than the other feeds. Higher assimilation efficiency was noticed in the animals provided with feeds 5 and 4. Higher gross arid net growth efficiencies were observed in the animals offered feed 1. Among the commercial feeds feed 3 may considered to be suitable alternative to feed 1. Keywords : Conversion efficiency, commercial & formulated feeds